Justice and strain-based conflict among Chinese prison staff - Liu, Jianhong (Psychology, crime & law, 2022)
Views of organizational justice among correctional staff (i.e. whether they perceive that their employing organization treats them fairly) impact both staff and prisons. The two major dimensions of organizational justice are distributive justice (fairness of outcomes) and procedural justice (fairness of processes and procedures). Limited research among correctional staff in the U.S. suggests that views of distributive and procedural justice spillover, which results in a strain-based form of work-family conflict. An ordinary least squares regression analysis of data collected from two prisons in southern China indicated that distributive justice had significant negative effects on the strain-based form of work-family conflict; however, contrary to findings among U.S. staff, procedural justice did not have a signification relationship with strain-based conflict. It appears that the connection between views of organizational justice and strain-based work-family conflict might vary by nation.